New protocol for cell culture to obtain mitotic chromosomes in fishes - Paim, Fabilene G. [UNESP]; Maia, Leandro [UNESP]; Landim-Alvarenga, Fernanda da Cruz [UNESP]; Foresti, Fausto [UNESP]; Oliveira, Claudio [UNESP] (MDPI, 2018)
Cell culture is an excellent alternative for the maintenance of cell lines and to obtain quality chromosome preparations of fishes. However, this methodology is still little employed, mainly because of the difficulty of standardization of cell cultures. In this study, we describe a methodology for the rapid acquisition of cell lineages and mitotic chromosomes for cytogenetic studies of fish species from muscle tissue cells. Our methodology is based on the use of a gelatin film, which provides better adhesion of a large number of cells and appropriate conditions for multiplication. The cells of Astyanax altiparanae, used as an experimental model, with fibroblast-like morphology, showed rapid cellular proliferation, resulting in a great number of cells. Chromosomal preparations of cultured cells showed the diploid number of the species, 2n = 50 chromosomes, in 80% of the cells examined, with chromosomes intact and distended. Cell populations were cryopreserved and after being recovered, these cells maintained their proliferative capacity. The development of this methodology represents an innovation for the fish cytogenetics area and it may bring a significant contribution to the conservation and study of several groups due to the difficulty of obtaining good-quality chromosome preparations.
Keywords: Cell culture; Chromosomes; Cryopreservation; Fish cytogenetic; Mitosis